Qlose: Program Repair with Quantiative Objectives - D'Antoni, Loris; Samanta, Roopsha; Singh, Rishabh (27th International Conference on Computer Aided Verification (CAV 2016), 2016)
The goal of automatic program repair is to identify a set of syntactic changes that can turn a program that is incorrect with respect to a given specification into a correct one. Existing program repair techniques typically aim to find any program that meets the given specification. Such "best-effort" strategies can end up generating a program that is quite different from the original one. Novel techniques have been proposed to compute syntactically minimal program fixes, but the smallest syntactic fix to a program can still significantly alter the original program's behavior. We propose a new approach to program repair based on program distances, which can quantify changes not only to the program syntax but also to the program semantics. We call this the quantitative program repair problem where the "optimal" repair is derived using multiple distances. We implement a solution to the quantitative repair problem in a prototype tool called (Quantitatively close), using the program synthesizer Sketch. We evaluate the effectiveness of different distances in obtaining desirable repairs by evaluating Qlose on programs taken from educational tools such as CodeHunt and edX.